Survey of depressive symptomatology in brain injury resulting from intimate partner violence. (28th January 2023) - Chiou, Kathy S.; Feiger, Jeremy A.; Cissne, Mackenzie; Garlinghouse, Matthew; Reisher, Peggy; Higgins, Kate; Rajaram, Shireen; DiLillo, David
ABSTRACT: Objective: A high prevalence of depression exists in specific sub-samples of survivors of brain injury (BI) sustained from intimate partner violence (IPV). However, the experience of depression by survivors of IPV-related BI from general civilian populations remains unclear. This study documents the symptom profile of depression reported by individuals who screened positive for sustaining an IPV-related BI. Methods: 36 individuals who screened positive for possible IPV-related BI completed the Beck Depression Inventory-2 nd Edition (BDI-II). Subscales characterizing the nature of the symptoms were created. Frequency and descriptive statistics were calculated for item responses on the BDI-II. Participants were also assigned to high or low symptom severity groups to examine between-group differences. Results: Participants endorsed experiencing somatic symptoms more severely than self-evaluative and affective symptoms. Additionally, self-evaluative and cognitive symptoms correlated with total BDI-II scores for the high symptom severity group but not for the low symptom severity group. Conclusions: The findings highlight somatic symptoms of depression, in particular as a common experience among survivors of IPV-related BI. Further, self-evaluative and cognitive symptoms may be more sensitive in detecting depression after IPV-related BI. These results may aid in the development of guidelines to better diagnose and treat depression in IPV-related BI.